DIGITAL TRANSFORMATION OF BANKING BUSINESS: PRESENT AND FUTURE - Kovalenko, Victoria; Sheludko, Sergii; Cherkashyna, Kateryna (Socio-economic relations in the digital society, 2023)
This article delves into the nuances of digital transformation within the realm of banking, prompted by the pervasive global digitization of economies. This phenomenon has profoundly shaped the trajectory of financial technologies, giving rise to innovative banking products. The primary objective of this study is to elucidate the essence of digital transformation and assess its efficacy in shaping the development of the banking sector.The digitization of banking involves the transformation of all associated processes and information. Consequently, the integration of digital technologies into the banking domain necessitates a comprehensive consideration of the needs of three key stakeholders: the consumer, the investor, and the bank itself. The authors conducted an analysis of the regulatory and legal landscape accompanying the digital transformation of the banking sector. The study concludes that the contemporary legal framework governing the use of digital technologies in banking is aligning with current global trends.The digital transformation of the banking industry is observed to manifest in several dimensions, encompassing remote and Internet banking, electronic payments, FinTech and innovation, blockchain and cryptocurrencies, cyber security systems, electronic identification and document circulation, as well as interoperability.The domestic banking system has exhibited noteworthy progress in digitalization in recent times. However, external factors, notably the incursion into Ukraine, have introduced certain adjustments. These include the outflow of intellectual human capital abroad, diminished financial literacy due to population migration, and the closure of bank outlets, particularly affecting territorial communities, especially rural areas, resulting in a loss of connectivity with banks.In light of these observations, it is asserted that future digital transformational endeavours in the banking sector should prioritize enhancing the financial literacy of consumers of banking services. Additionally, there is a need to fortify regulatory frameworks governing the cryptocurrency market in Ukraine and establish unified standards for the regulation and supervision of banks and FinTech companies providing digital financial services.
Keywords: digital transformation; banking business; financial technologies; electronic banking services; mobile banking; Internet banking; electronic payments; blockchain; cryptocurrency; cyber security; electronic identification; interoperability